Radioprotective effect of polyvinylpyrrolidone modified selenium nanoparticles and its antioxidation mechanism in vitro and in vivo - Li, Wei; Lu, Xianzhou; Jiang, Liangjun; Wang, Xiangjiang (Frontiers in Bioengineering and Biotechnology, 2024)
Objective: Polyvinylpyrrolidone (PVP) is a commonly used biomedical polymer material with good water solubility, biocompatibility, low immunogenicity, and low toxicity. The aim of this study is to investigate the antioxidant mechanism and clinical potential of PVP modified selenium nanoparticles (PVP-Se NPs) as a new radioprotective agent. Methods: A laser particle size analyzer and transmission electron microscope were used to characterize PVP-Se nanoparticles prepared by chemical reduction. Human umbilical vein endothelial cells (HUVECs) were used to evaluate the radiation protective effects of PVP-Se NPs. SD rats were employed as an in vivo model to identify the most effective concentration of PVP-Se NPs and assess their potential radioprotective properties. Western blot (WB) was used to detect the expression of nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling proteins in human umbilical vein endothelial cells (HUVECs) and rat liver and kidney tissues. Results: PVP-Se NPs could reduce the oxidative stress injury and inflammatory response caused by X-ray irradiation in HUVECs and rats, and inhibit cell apoptosis by modulating NF-κB and MAPK signaling pathways. PVP-Se NPs could increase HUVECs viability, reduce apoptosis, inhibit inflammatory factors IL-1β, IL-6 and TNF-α, improve the survival rate of rats, promote antioxidant enzyme activities in cells and rats, reduce malondialdehyde concentration in serum, and reduce the expression of inflammatory factors such as IL-1β, IL-6 and TNF-α in cell supernatant and liver and kidney tissues. PVP-Se NPs could significantly reduce the phosphorylation levels of NF-κB and MAPK pathway-associated proteins in HUVECs and rat liver and kidney tissues (P<0.05). Conclusion: PVP-Se NPs can protect against radiation-induced oxidative damage by modulating NF-kB and MAPK pathways, providing a theoretical basis and experimental data for their use as an effective radioprotective agent.